IMPROVING STUDENTS’ WRITING SKILL ON DESCRIPTIVE TEXT BY ESTAFET STRATEGY OF THE ELEVENTH YEAR STUDENTS OF SMA 4 PALOPO - Dewi Furwana; Andi Tenrisanna Syam (Institut Agama Islam Negeri Palopo, 2019)
The objective of the research was to find out whether estafet strategy is effective to improve students’ writing skill on descriptive text of the eleventh year students’ of SMAN 4 Palopo. This research usedquasi experimental.The population of this research was the eleventh grade students of SMAN 4 Palopo. The number of population was 50 students. The sample were class XI PS 1 consisted of 25 students as experimental group and class XI PS 2 consisted of 25 students as control class.The sampling technique in this research was purposive sampling. The instrument of the research was writing test. The writers gave pretest and posttest to the students. The result showed that the students` mean score of posttest in experimental group was 90.44 and pretest was 65.96. The mean score of posttest was higher than the mean score of pretest (90.44>65.96). While the mean score of posttest in control class was 75.76 and the mean score of pretest was 60.52. The mean score of posttest was higher than the mean score of pretest (75.76>60.52). The result of statistical analysis the experimental group for level of significance 0.05 with degree of freedom (df) = 24; the probability value was smaller than α 0.00<0.5 and the result of statistical analysis the control class in which the probability value was lower than α .0.00>0.05. As a result, there was a significant difference in writing achievement between the students who are taught by using estafet strategy and those who are taught by non-using estafet strategy. Based on the result of this research, the writers concluded that estafet strategy upgrades the students’ writing.